NALCN channels enhance the intrinsic excitability of spinal projection neurons. Issue 9 (September 2018) - Ford, Neil C.; Ren, Dejian; Baccei, Mark L.
Abstract : Abstract: Spinal projection neurons convey nociceptive signals to multiple brain regions including the parabrachial (PB) nucleus, which contributes to the emotional valence of pain perception. Despite the clear importance of projection neurons to pain processing, our understanding of the factors that shape their intrinsic membrane excitability remains limited. Here, we investigate a potential role for the Na + leak channel NALCN in regulating the activity of spino-PB neurons in the developing rodent. Pharmacological reduction of NALCN current (INALCN ), or the genetic deletion of NALCN channels, significantly reduced the intrinsic excitability of lamina I spino-PB neurons. In addition, substance P (SP) activated INALCN in ascending projection neurons through downstream Src kinase signaling, and the knockout of NALCN prevented SP-evoked action potential discharge in this neuronal population. These results identify, for the first time, NALCN as a strong regulator of neuronal activity within central pain circuits and also elucidate an additional ionic mechanism by which SP can modulate spinal nociceptive processing. Collectively, these findings indicate that the level of NALCN conductance within spino-PB neurons tightly governs ascending nociceptive transmission to the brain and thereby potentially influences pain perception. Abstract : The nonselective sodium leak channel (NALCN) enhances the intrinsic excitability of rodent lamina I spino-parabrachial neurons and is activated by substance P through Src kinases.